Türkiye vakıflarında stratejik yönetim : stratejik yönetim ekolleri üzerinden bir değerlendirme - Gül, Zehra (My University, 2025)
Türkiye vakıflarında stratejik yönetim : stratejik yönetim ekolleri üzerinden bir değerlendirme Türkiye'deki vakıfların stratejik yönetim süreçlerini inceleyen bu araştırma, Mintzberg'in Stratejik Yönetim Okulları perspektifinden hareketle söz konusu kurumların stratejik planlama, karar alma, uygulama ve değerlendirme yaklaşımlarını analiz etmektedir. Nitel araştırma yöntemi kapsamında durum çalışması modeliyle tasarlanan çalışmada, amaçlı ve kartopu örnekleme teknikleri kullanılarak eğitim, sosyal yardım, kültür, sağlık, girişimcilik ve kapasite geliştirme gibi farklı alanlarda İstanbul’da faaliyet gösteren 21 vakıf yöneticisiyle yarı yapılandırılmış görüşmeler gerçekleştirilmiştir. İstanbul'da faaliyet gösteren vakıfların stratejik yönetim süreçlerini derinlemesine anlamak amacıyla toplanan veriler, MAXQDA Analytics Pro 2020 yazılımıyla tematik analize tabi tutulmuştur. Araştırma bulguları, vakıfların stratejik yönetiminde tek bir ekole bağlı kalmadığını, aksine Tasarım ve Planlama Okullarının biçimsel yönleriyle Kültürel, Öğrenme, Bilişsel ve Girişimcilik Okullarının esnek ve değer temelli yaklaşımlarını bütünleştiren melez bir stratejik yapı benimsediğini ortaya koymaktadır. Bu durum, vakıfların hem kurumsal kimlik ve geleneklerini koruyan hem de çevresel değişimlere uyum sağlayan dinamik ve öğrenen bir stratejik yönetim anlayışına sahip olduklarını göstermektedir.

Strategic management in Turkish foundations : an approach based on strategic management schools This research, which examines the strategic management processes of foundations in Türkiye, draws on Mintzberg's Strategic Management Schools perspective and analyzes the strategic planning, decision-making, implementation, and evaluation approaches of these institutions. Designed with a case study model within the scope of qualitative research methods, the study employed purposive and snowball sampling techniques to conduct semi-structured interviews with 21 foundation managers operating in Istanbul in various fields such as education, social assistance, culture, health, entrepreneurship, and capacity building. To gain an in-depth understanding of the strategic management processes of foundations operating in Istanbul, the collected data was subjected to thematic analysis using MAXQDA Analytics Pro 2020 software. The research findings reveal that foundations do not adhere to a single school of thought in their strategic management; rather, they adopt a hybrid strategic structure that integrates the formal aspects of Design and Planning schools with the flexible and value-based approaches of Cultural, Learning, Cognitive, and Entrepreneurial schools. This demonstrates that foundations possess a dynamic and learning strategic management approach that both preserves their corporate identity and traditions and adapts to environmental changes.
Strategic management in Turkish foundations : an approach based on strategic management schools
Keywords: Endowments; Foundation; Management; Mintzberg Strategic Schools; Mintzberg Stratejik Okulları; Nitel Araştırma; Qualitative Research; Strategic Management; Strategy; Strateji; Stratejik Yönetim; Vakıf; Vakıflar; Yönetim